Forensic veterinary examination of defeat of the dogs, cats and other animals as a result of electric shock - Bokotko, R.; Harkusha, S.; Kruchynenko, O.; Peredera О. (Scientific Progress & Innovations, 2024)
One of the harmful physical factors that negatively affect a living organism is electric current. It affects animals through both direct and indirect contact. The purpose of the study is to systematize the currently available information on electric shocks to animals in terms of forensic veterinary research. There are two types of electric shocks: technical and natural. The most common type of electrocution is by technical current, either direct or alternating. It occurs when the body of animals comes into contact with objects that are conductors of live current, with faulty electrical appliances and electrical equipment. In the area of powerful electromagnetic fields due to damage to high-voltage electrical equipment, damage can occur even in the absence of direct contact. There are three types of effects of technical electric current on a living organism: electrochemical, thermal, and mechanical. Both in living animals and in dead animals, specific changes in the discharge gate (electromark), burns, mechanical damage to the skin, muscles and internal organs, tissue stratification at the microscopic level, and in case of death, signs of primary cardiac arrest, lack of blood clotting, venous and arterial hyperemia of internal organs are detected on the body. In the case of an atmospheric electric discharge, tissue carbonization, lightning, mechanical damage, charring, tearing of body parts, and tearing of the body into separate fragments are detected. The forensic veterinarian should keep in mind that death from electrocution is often sudden and there is no history. Damage from electric shock is difficult to treat and difficult to prevent. Therefore, it is necessary to differentiate electrocution of animals from diseases of a different nature and pathological processes that can also lead to sudden death. Inspection of the scene is also important, especially in the case of natural electric shock. The question arises as to the presence or absence of criminal negligence in the actions of persons responsible for the serviceability of electrical equipment in places where animals are kept. Thus, the effect of electric current on animals is a set of specific clinical and anatomical changes in the animal’s body that occur under the influence of an electric discharge of man-made or natural origin.